Критерії відбору текстів з наукового стилю мовлення (довузівський етап мовної підготовки) - Манаева, Галина Сергіївна; Новікова, Ірина Георгіївна (Munich : MDPC Publishing, 2021)
Annotation. The purpose of this article is to determine the criteria for selecting textual material that is optimal for teaching reading Ukrainian language to foreign students at the initial stage of study. The article provides the criteria by which the communicative goal can be achieved - preparation of foreign students to read literature in the specialty: 1. motivational (cognitive) factor; 2. Interest as a selection factor; 3. Thematic compliance of the specialization profile; 4. Availability of content; 5. The easiness of the lexical and grammatical material included in the text. According to the authors of this article, the use of these criteria in the selection of texts will serve as a reliable basis for creating a typology of educational texts in the language of the specialty.